Direct fluorescent glycan labeling with recombinant sialyltransferases. (30th July 2019) - Wu, Zhengliang L; Person, Anthony D; Burton, Andrew J; Singh, Ravinder; Burroughs, Barbara; Fryxell, Dan; Tatge, Timothy J; Manning, Timothy; Wu, Guoping; Swift, Karl A D; Kalabokis, Vassili
Abstract: Glycosylation is a common modification found on numerous proteins and lipids. However, direct detection of glycans on these intact biomolecules has been challenge. Here, utilizing enzymatic incorporation of fluorophore-conjugated sialic acids, dubbed as direct fluorescent glycan labeling, we report the labeling and detection of N- and O-glycans on glycoproteins. The method allows detection of specific glycans without the laborious gel blotting and chemiluminescence reactions used in Western blotting. The method can also be used with a variety of fluorescent dyes.